First record of Megacydnus secundus J. A. Lis, 2002, a representative of Afrotropical endemic burrower bug genus from Uganda, and an annotated checklist of Ugandan Cydnidae (Hemiptera: Heteroptera) - Lis, Jerzy A.; Lis, Barbara (Zootaxa, 2014)
The Cydnidae (Hemiptera: Heteroptera: Pentatomoidea) is a true bug family with almost 700 species distributed worldwide (Lis 1996, 1999, 2006). These bugs usually dig in the ground (e.g., sand, soil, litter) and, therefore, are commonly known as the burrower bugs or burrowing bugs. Digging in the ground is possible because of several morphological adaptations, including well-developed tibial combs (Lis and Schaefer 2005), coxal combs (Lis 2010), and strong hair-like and peg-like setae on the head margins in larval and adult stages (Lis and Pluot-Sigwalt 2002) (see: Fig. 1A).